Pemberdayaan Masyarakat Desa Pangkil melalui Inovasi Brownies Fortifikasi Tepung Ikan Rucah untuk Peningkatan Nilai Tambah - Manullang, Benny; Prastari, Cindytia; Ilhamdy, Aidil Fadli; Seulalae, Anggrei Viona; Jumsurizal, Jumsurizal; Putri, R Marwita Sari; Rahman, R Fathul; Amrizal, Sri Novalina; Viruly, Lily; Oktavia, Yulia; Apriandi, Azwin; Harefa, Sedianto; Darmawan, Faiz Maulana; Armandaris, Muhammad Ja’far; Fitri, Syarifah Aida; Istiqhomah, Istiqhomah (PRIMA: Journal of Community Empowering and Services, 2026)
Empowering The Pangkil Village Community Through Innovation of Fortified Brownies Made from By-catch Fish Flour. Pangkil Village, Teluk Bintan District is one of the small islands in the Riau Islands Province that has abundant fishery potential, including bycatch fish, but has not been optimally utilized. Bycatch fish have great potential as cheap and highly nutritious fortified food ingredients in the form of fish meal. This activity aims to improve the knowledge and skills of the Pangkil Village community in processing bycatch fish into innovative products in the form of bycatch fish meal fortified fudgy brownies and to increase the added value of local fishery products. The methods used included socialization, training in making bycatch fish meal-fortified fudgy brownies, organoleptic testing, and activity evaluation. The preparation of fudgy brownies is divided into three parts: preparation of chocolate dough, egg dough, and addition of wheat flour and bycatch fish meal. The resulting fudgy brownies had a whole appearance, a slightly dense texture from the outside but soft inside, chocolate aroma, sweet taste, and brown color. The results of the organoleptic test showed that the panelists liked the bycatch fish meal fortified fudgy brownies in all sensory attributes. The questionnaire analysis results showed that the average training achievement score was 4.42, which fell into the "agree-strongly agree" category. This value indicates that the training activities were effective and well received by the participants. The results of the activity benefit test showed that p>0.05. This indicates that the benefits of the training were felt equally by all participants, both experienced and beginner. These findings indicate that the participatory training methods and hands-on practice used were able to reach all participants equally well. Overall, this activity has contributed to improving the economy of coastal communities and developing local potential based on fishery products.